Design and development of hovercraft amphibious robot locomotion for unmanned missions - M. Yusof, M. S.; Rafeeq, M.; Toha, Siti Fauziah (Penerbit Universiti Teknikal Malaysia Melaka, 2023)
Unmanned aerial vehicles have been popular for unmanned missions like monitoring, data collection, and rescue operation. These wide varieties of applications in military, search and rescue, and civil areas require the unmanned vehicle to traverse multiple environments such as land, water, and air. However, Unmanned vehicle maneuvering in these dynamic and unstructured environments increases the complexity of the design and development of Unmanned vehicles. Thus, there is a requirement to design simpler models, lower control capability, and prototype development with lower hardware requirements. The study aims to design and develop an amphibious vehicle integrating hovercraft capability that allows the system to traverse in a different environment with a lower transformation mechanism and simpler control design. The Hovercraft amphibious robot is designed using Solidworks, and a prototype is developed. For the evolved design and the functionality of the developed system is evaluated. The hovercraft was lifted and was propelled by the thrust system. It was able to carry craft weight 1.34 kg and hovered with an air cushion of 0.5 inch. The developed system with an IoT system plugin will serve in the data collection, sample collection, and monitoring of disaster-prone water bodies and amphibious reconnaissance missions.